Pre-Service Teachers’ Reflective Practice and their Teaching Practicum Beliefs - Arlon Ponce Cadiz (JURNAL INOVATIF ILMU PENDIDIKAN, 2021)
While learning assessment serves as feedback for teachers in maintaining or improving teaching practice, reflective practice play can be seen in how pre-service teachers plan, design, implement and evaluate their teaching approaches. Practicing reflection can help pre-service teachers starting to embrace the value and passion of teaching which manifests in their professional teaching practice. This study was conducted to determine the reflective practice of pre-service teachers and their teaching practicum experience. Involved in this study were 103 pre-service teachers from the government Teacher Education Institution. The study used self-developed survey questionnaires on pre-service reflective practice and beliefs about their teaching practicum. Results showed that there is a significant relationship between the reflective practice of pre-service teachers and their beliefs about teaching practicum. On the other hand, reflective practice as well as the beliefs of male and female pre-service teachers about their teaching practicum does not have a significant difference. Teacher educators should impart reflective practice as part of their teaching practicum. For further research, a wide scope of study may be conducted involving different Teacher Education Institutions in private and public Higher Education Institutions to verify the findings in this study.Keywords: pre-service teachers, reflective practice, teaching practicumDOI: http://dx.doi.org/10.23960/jiip.v3i2.22854